Receptor Site on Clover and Alfalfa Roots for Rhizobium - Dazzo, Frank B. (1977)
Sites on white clover and alfalfa roots that bind Rhizobium trifolii and R. meliloti capsular polysaccharides, respectively, were examined by fluorescence microscopy. Fluorescein isothiocyanate-labeled capsular material from R. trifolii bound specifically to root hairs of clover but not alfalfa. Binding was most intense at the root hair tips. Treatment of clover roots with 2-deoxyglucose (2-dG) prevented binding of R. trifolii capsular material to the roots. The sugar 2-dG enhanced the elution of clover root protein, which could bind to and specifically agglutinate R. trifolii but not R. meliloti or R. japonicum. The mild elution procedure left the roots intact. Agglutination of R. trifolii and passive hemagglutination of rabbit erythrocytes coated with the capsular material of R. trifolii were specifically inhibited by 2-dG. These results suggest that clover roots contain proteins that cross-link complementary polysaccharides on the surface of clover root hairs and infective R. trifolii through 2-dG-sensitive binding sites. Alfalfa root hairs were shown to specifically bind to a surface polysaccharide from R. meliloti.